Clinical validation of the Lumipulse G β‐amyloid ratio (1‐42/1‐40) in a subset of ADNI CSF samples. (31st December 2021) - Esquivel, Rianne N.; Benina, Natalya; Hawkins, Douglas M.; De Simone, Francesca; Le Bastard, Nathalie; Vandijck, Manu; Gannon, Sara; Latham, Jessica; Radwan, Rachel R.; Dickson, Diana
Abstract: Background: The CSF Lumipulse G β‐Amyloid Ratio (1‐42/1‐40) provides a potential alternative to amyloid PET testing for patients with cognitive impairment to receive an assessment of their amyloid status. Clinical validation of amyloid CSF biomarkers for Alzheimer's Disease (AD) is critical to ensure accurate assessment of patients. A cutoff of 0.058 was previously established in the Amsterdam Dementia Cohort consisting of 235 individuals with various cognitive complaints and corresponding amyloid PET imaging results. Here we present clinical validation of the cutoff in a blinded clinical study of Alzheimer's Disease Neuroimaging Initiative (ADNI) CSF samples measured on the Lumipulse G1200. Method: A subset of CSF samples from the ADNI biobank was used to validate the cutoff of 0.058. Samples included had amyloid PET images derived from an FDA approved tracer (Florbetapir F18) and method and subjects were ≥50 years (n=274). Demographics included 69% amyloid‐PET positive; mean age 73 years; 44% female; MMSE range 12‐30; and diagnoses: mild cognitive impairment (n=170) or AD (n=104). CSF Aβ42 and Aβ40 were measured using the LUMIPULSE G1200 (Fujirebio). Positive and negative percent agreement (PPA and NPA) and Overall Percent Agreement (OPA) were calculated based on agreement with PET imaging results. Three independent neuroradiologists (2 readers and an adjudicator, when necessary) blinded to all other clinical data, reviewed the scans and provided a visual interpretation according to FDA‐approved labeling. The adjudicated PET read was used in the analysis. Clinical data for the ADNI samples were not received until after testing was completed. Result: At a set cutoff of 0.058 the Lumipulse G β‐Amyloid Ratio (1‐42/1‐40) demonstrated a PPA and NPA of 86.3% (CI 80.7% – 90.5%) and 92.9% (CI 85.3% – 96.7%) respectively with an OPA of 88.3% (CI 84.0%‐91.6%). Conclusion: The Lumipulse G β‐Amyloid Ratio (1‐42/1‐40) ratio strongly correlates with PET status. Performance of the CSF Aβ42/Aβ40 ratio reflects published agreement obtained by readers when interpreting PET images. Importantly, use of the CSF ratio can reduce costs to patients and provide greater ease of access to testing. In conjunction with clinical assessment the Aβ42/Aβ40 ratio can serve as a highly effective biomarker to assess amyloid status.